2019
DOI: 10.1016/j.joca.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cartilage thickness and subchondral bone mineral density in non-osteoarthritic and severely osteoarthritic knees: In vivo concomitant 3D analysis using CT arthrography

Abstract: s u m m a r yObjective: To test whether subchondral bone mineral density (sBMD) and cartilage thickness (CTh) of femoral condyles are correlated in knees without and with severe medial femorotibial osteoarthritis (OA), using a subregional analysis with computerized tomography (CT) arthrography. Methods: CT arthrograms of 50 non-OA (18 males, 58.7 (interquartile range (IQR) ¼ 6.6 years)) and 50 severe medial OA (24 males, 60.5 (IQR ¼ 10.7) years) knees, were retrospectively analyzed. Bone and cartilage were seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…Thinner cartilage was associated with denser subchondral bone in OA knees, while thicker cartilage was associated with denser subchondral bone in control knees. The results support the theory that OA disrupts the normal homeostatic relationship between cartilage and subchondral bone 47 . Dube et al used statistical shape modeling of MRI to investigate changes in femur and tibia morphology over 24 months in 600 subjects from the OAI.…”
Section: Bone In Knee Oasupporting
confidence: 84%
“…Thinner cartilage was associated with denser subchondral bone in OA knees, while thicker cartilage was associated with denser subchondral bone in control knees. The results support the theory that OA disrupts the normal homeostatic relationship between cartilage and subchondral bone 47 . Dube et al used statistical shape modeling of MRI to investigate changes in femur and tibia morphology over 24 months in 600 subjects from the OAI.…”
Section: Bone In Knee Oasupporting
confidence: 84%
“…The relationship between subchondral bone degeneration and OA severity has previously been reported in several studies. Among them, Omoumi et al [13] have shown that in knee OA, cartilage thickness and subchondral bone mineral density based on CT arthrography are negatively correlated, which indicate mutual adaptation in cartilage-subchondral bone loses in the OA state. Bobinac et al [33] showed the same trends as reported in the current study in subchondral bone and cartilage degeneration under OA; however, they used a 2D histology method for STB microarchitecture and did not consider the effect of knee alignment changes.…”
Section: Discussionmentioning
confidence: 99%
“…The properties and structure of the STB in OA could be characterized by dual X-ray absorptiometry (DXA) [11], X-ray computed tomography (CT) [12], CT arthrography [13], micro-CT (μCT) [14], and magnetic resonance imaging (MRI) [15,16]. Previous studies have reported that knee OA severity, based on histological score [17], Kellgren-Lawrence (K-L) grade [18], cartilage defects, and cartilage thinning, was positively correlated with tibial plateau subchondral bone mineral density (BMD), trabecular bone volume fraction (BV/TV), trabecular number (Tb.N), and trabecular thickness (Tb.Th), suggesting that subchondral bone is closely related to OA severity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, substantial evidence has shown that subchondral bone and cartilage are a closely related integrated unit and mutually adaptable [17][18][19]. In the early stage of KOA, the absorption of subchondral bone is enhanced, and the mechanical strength of the bone is reduced.…”
Section: Discussionmentioning
confidence: 99%